1983
DOI: 10.1159/000117970
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Midazolam in Conjunction with Alcohol on Iconic Memory and Free-Recall

Abstract: The effects of midazolam 15 mg and alcohol 0.5 g/kg on short-term storage in the visual system (iconic memory) and free recall of a word list were investigated in 8 normal volunteers. Acute doses of midazolam, alcohol and midazolam in combination with alcohol were all found to decrease iconic memory whereas only midazolam and midazolam + alcohol impaired immediate recall. Anterograde amnesia was observed following treatment with midazolam and midazolam in conjunction with alcohol. The results suggest a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Subjects were signi®cantly impaired after the alcohol, as shown by the examiners' ratings, despite subjective ratings from the volunteer drivers indicating that they did not feel their driving to have been aected. Closed course studies (on non-public tracks) have also shown dose-related impairment on various types of driving task, comparable to the results of simulator studies (Huntley, 1973;Hindmarch and Subhan, 1983;Gawron and Ranney, 1988;Starmer, 1990).…”
Section: Alcohol and Car Drivingsupporting
confidence: 66%
See 1 more Smart Citation
“…Subjects were signi®cantly impaired after the alcohol, as shown by the examiners' ratings, despite subjective ratings from the volunteer drivers indicating that they did not feel their driving to have been aected. Closed course studies (on non-public tracks) have also shown dose-related impairment on various types of driving task, comparable to the results of simulator studies (Huntley, 1973;Hindmarch and Subhan, 1983;Gawron and Ranney, 1988;Starmer, 1990).…”
Section: Alcohol and Car Drivingsupporting
confidence: 66%
“…A number of measures of performance have been used, and shown to be aected by modest doses of alcohol (Drew et al, 1958;Gawron and Ranney, 1988). These include brake reaction time (Hindmarch and Subhan, 1983)`collision' frequency (Linnoila and Mattila, 1973;Laurell and Tornros, 1982) steering responsiveness and lane control (Mortimer and Sturgis, 1972;Allen et al, 1975;Smiley et al, 1985), as well as more`global' ratings of driving ability. Apart from actual ability to control the vehicle, alcohol can aect other aspects of car driving behaviour, whether simulated or not, such as forward planning, decision making, aggressiveness and risk-taking.…”
Section: Alcohol and Car Drivingmentioning
confidence: 99%
“…ings corroborate and extend those of other investigators who found the duration of anterograde amnesia to be 20-30 min after midazolam, 5 mg intravenously (Conner et al, 1980;Dundee & Wilson, 1980) and at least 1 h after 15 mg orally )btained in (Subhan & Hindmarch, 1983). In our more exi the results tensive memory testing we found that the anxnen et al, terograde amnesic effect of 15 mg of midazolam, pid absorp-by either route of administration, lasts at least 90 am is only min.…”
Section: Resultssupporting
confidence: 89%
“…Because if subjective time passes more slowly the standard as well as the comparison interval would be affected equally and, therefore, resulting threshold values should remain unchanged. Since benzodiazepines are known to directly affect memory functions (Bixler et al, 1979;McKay and Dundee, 1980;Subhan and Hindmarch, 1983;Subhan, 1984;Curran and Birch, 1991;File, 1992) the observed decrease in performance on time estimation under midazolam may be more likely due to its immediate impairing effect on memory processes. In this respect, reduced performance integrity can be considered a consequence of pharmacologically induced deterioration of memory functions that result in a more variable cognitive representation of the durations to be compared and, thus, significantly decreasing task accuracy.…”
Section: Effects Of Midazolam and Placebo On Performance On Temporalmentioning
confidence: 99%
“…A second purpose of this study was to provide some evidence for the notion of two distinct timing mechanisms underlying time estimation and time perception. Since time estimation is cognitively mediated, we would predict that performance on time estimation would be adversely affected by midazolam due to its sedative properties and the impairing effects of midazolam on cognitive information processing (Subhan and Hindmarch, 1983;Hennessy et al, 1991;File, 1992;File et al, 1992). On the other hand, performance on time perception should not be expected to deteriorate if the assumed neural timing mechanism underlying temporal processing of brief intervals in the range of milliseconds is not prone to changes in cortical arousal and if temporal processing of brief durations does not depend on cognitive mechanisms.…”
Section: Introductionmentioning
confidence: 99%